The Implementation of Lease Agreements for Village Treasury/Cash Land by the Government - Yuliasari, Euis (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
The purpose of this research to study the implementation of the lease agreement on village treasury land carried out by the Pamengkang Village Government and State Junior High School of 2 Mundu Cirebon Regency, as well as to study the management and utilization of village treasury land which was leased to State Junior High School of 2 Mundu Cirebon Regency. This research method uses descriptive analysis. The specifications of the research used are library research, interview techniques and document studies. Source of data used in the form of primary data obtained by interview results. Based on the results of the study, it was concluded: 1) the implementation of the lease agreement on village treasury land by the Pamengkang Village Government and State Junior High School of 2 Mundu Cirebon Regency with the approval of the BPD (Village Consultative Body). Leases are made for a certain period of time, rental period of 1 year. Each year the agreement is renewed with a different price agreement. The Pamengkang village government annually submits a proposal to the school for an increase in the price of land rent, and the school negotiates with the Pamengkang village government to agree on a price to be agreed upon that year as outlined in the agreement. 2) management and utilization of village treasury land that is leased out for the management of the land is carried out for the public interest and the village's original income. The Pamengkang village government only provides the enjoyment/use of the land for a certain period of time, or in other words, the owner only hands over power over the goods by way of leasing, not to own it.Keywords: Agreement; Lease; Treasury; Utilization; Village